Design, fabrication and characterization of LTCC micro-hotplates for gas-sensing application. Issue 1 (23rd December 2019) - Kulhari, Lokesh; Chandran, Achu; Ray, Kanad; Khanna, P.K.
Abstract : Purpose: Low temperature co-fired ceramics (LTCC) technology-based micro-hotplates are of immense interest owing to their ruggedness, high temperature stability and reliability. The purpose of this paper is to study the role of thermal mass of LTCC-based micro-hotplates on the power consumption and temperature for gas-sensing applications. Design/methodology/approach: The LTCC micro-hotplates with different thicknesses are designed and fabricated. The role of thermal mass on power consumption and temperature of these hotplates are simulated and experimentally studied. Also, a comparison study on the performance of LTCC and alumina-based hotplates of equivalent thickness is done. A thick film-sensing layer of tin oxide is coated on LTCC micro-hotplate and demonstrated for the sensing of commercial liquefied petroleum gas. Findings: It is found from both simulation and experimental studies that the power consumption of LTCC hotplates was decreasing with the decrease in thermal mass to attain the same temperature. Also, the LTCC hotplates are less power-consuming than alumina-based one, owing to their superior thermal characteristics (low thermal conductivity, 3.3 W/ [m-K]). Originality/value: This study will be beneficial for designing hotplates based on LTCC technology with low power consumption and better stability for gas-sensing applications.